FTIR Spectroscopic Study of the Secondary Structure of Globular Proteins in Aqueous Protic Ionic Liquids - Arunkumar, Radhika; Drummond, Calum J.; Greaves, Tamar L. (Frontiers in Chemistry, 2019)
Protein misfolding is a detrimental effect which can lead to the inactivation of enzymes, aggregation and the formation of insoluble protein fibrils called Amyloids. Consequently, it is important to understand the mechanism of protein folding, and under which conditions it can be avoided or mitigated. Ionic liquids (ILs) have previously been shown as capable of increasing or decreasing protein stability depending on the specific IL, IL concentration and which protein. However, a greater range of IL-proteins need to be systematically explored to enable structure-property relationships to be developed. In this work, the secondary structure of four proteins, lysozyme, trypsin, β-lactoglobulin and α-amylase, were studied in aqueous solutions of 10 protic ionic liquids (PILs) with 0 to 50 mol% PIL present. The PILs consisted of ethyl-, ethanol-, diethanol- and triethanolammonium cations paired with nitrate, formate, acetate or glycolate anions. The secondary structure was obtained using ATR-FTIR spectroscopy. Lysozyme and trypsin retained secondary structure consistent with a native folded state for many of the aqueous IL solutions which contained a formate or nitrate anion at 5 mol% IL. In contrast, α-amylase and β-lactoglobulin generally had poor stability and solubility in the IL solutions. This may be due to the isoelectric point of α-amylase and β-lactoglobulin being closer to the pH of the solvents. All four proteins were insoluble in ethyl-, ethanol- and diethanolammonium acetate, though α-amylase and trypsin retained their secondary structure in up to 20 and 30 mol% of triethanolammonium acetate respectively. It was evident that the protein stability varied substantially depending on the protein-IL combination, and the IL concentration in water. Overall, the findings indicated that some ions and ILs were better for protein solubility and stability than others, such as acetate leading to poor solubility, and EAN and EAF generally leading to better protein stability than the other PILs. This study of 4 proteins in 10 aqueous PILs clearly showed there are many complexities in the interactions and no clear trends, despite the similarities between the PIL structures. This highlights the need for more large studies to enable the selection and optimisation of PIL solvents for use with biomolecules.